Renovation of the Church - Mumbai Archive Project Team (Jio Institute, 2024)
Between 1924-25, the church was extended to accommodate the increasing number of people. The church was completely remodelled during the Vicarship of Msgr. Stanislaus Pereira to give it a modern appearance.